Deterioration of Concrete Under Simulated Acid Rain Conditions: Microstructure, Appearance, and Compressive Properties - Lingxu Li; Norazura Muhamad Bunnori; Chee Ghuan Tan (Buildings)
The effects of acid rain corrosion on the properties of concrete are broadly understood. This study investigated the impact of varying corrosion conditions on the microstructure and mechanical properties of concrete, which has not received sufficient attention using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and compressive tests. In the laboratory, simulated acid rain solutions with pH levels of 0.0, 1.0, and 2.0 were prepared using sulfuric acid solution. A total of 13 sets of 39 concrete cubes each were immersed in these acid solutions for durations of 7, 14, 21, and 28 days. The findings clearly indicate that simulated acid rain corrosion significantly affects both the microstructure and mechanical properties of concrete. Acid alters the material composition of concrete and simultaneously increases the formation of pores within it. This not only changes the number, area, and perimeter of the pores but also affects their shape parameters, including circularity and fractal box-counting dimension. These pores typically measure less than 0.4 μm and include micro- and medium-sized pores, contributing to the more porous and structurally loose concrete matrix. As the duration of acid exposure and the concentration of the acid solution increase, there is noticeable decrease in compressive strength, accompanied by changes in the concrete structure. The rate of strength reduction varies from 6.05% to 37.90%. The corrosion process of acid solution on concrete is characterized by a gradual advancement of the corrosion front. However, this progression slows over time because as the corrosion depth increases, the penetration of the acid solution into deeper layers becomes limited, thereby reducing the rate of strength deterioration. The deterioration mechanism of concrete can be attributed to dissolution corrosion caused by H+ ions and expansion corrosion due to the coupling of SO42− ions.